Business analysis and valuation : text and cases - Bernard, Victor Lewis, 1952-1995; Healy, Paul M., 1956-; Palepu, Krishna G., 1954- (London : Thomson learning, 2007)
PART I: FRAMEWORK. 1. A Framework for Business Analysis and Valuation Using Financial Statements. PART II: BUSINESS ANALYSIS AND VALUATION TOOLS. 2. Strategy Analysis. 3. Overview of Accounting Analysis. 4. Implementing Accounting Analysis. 5. Financial Analysis. 6. Prospective Analysis: Forecasting. 7. Prospective Analysis: Valuation Theory and Concepts. 8. Prospective Analysis: Valuation Implementation. PART III: BUSINESS ANALYSIS AND VALUATION APPLICATIONS. 9. Equity Security Analysis. 10. Credit Analysis and Distress Prediction. 11. Mergers and Acquisitions. 12. Corporate Financing Policies. 13. Communication and Governance. PART IV: ADDITIONAL CASES. 1. Amazon.com in the Year 2000. 2. Anacomp, Inc. 3. Home Depot, Inc. in the New Millennium. 4. Krispy Kreme Doughnuts. 5. Pre-Paid Legal Services, Inc. 6. Schneider and Square D. 7. Spyker Cars N.V. 8. The Home Depot, Inc. 9. Two European Hotel Groups (A): Equity Analysis. 10. Two European Hotel Groups (B): Debt Analysis. 11. United Parcel Service's IPO. 12. Valuation Ratios in the Airline Industry. Index. Author index.
Keywords: Ondernemingen ; financiële analyse